2017
DOI: 10.5770/cgj.20.248
|View full text |Cite
|
Sign up to set email alerts
|

Planning Health Services for Seniors: Can We Use Patient’s Own Perception?

Abstract: ObjectivesThe objectives of this study were to identify needs and to estimate whether self-reported health can be used as an indicator of service needs among seniors.MethodsThis was a cross-sectional survey. Age- and sex-adjusted logistic regression was used to estimate the link between functional status indicators and fair or poor self-reported health. Forward stepwise logistic regression was performed to identify the strongest contributors of poor health. Positive predictive value (PPV), sensitivity, and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…Our study indicated no association between SRH and participation in medical rehabilitation, whereas Figueiredo et al [ 39 ] found SRH to be a useful tool for evaluating medical service needs among older adults discharged from the hospital. Potential reason for the aforementioned difference could be the methodology of presented surveys since the PolSenior study group comprised of community dwellers.…”
Section: Discussioncontrasting
confidence: 83%
“…Our study indicated no association between SRH and participation in medical rehabilitation, whereas Figueiredo et al [ 39 ] found SRH to be a useful tool for evaluating medical service needs among older adults discharged from the hospital. Potential reason for the aforementioned difference could be the methodology of presented surveys since the PolSenior study group comprised of community dwellers.…”
Section: Discussioncontrasting
confidence: 83%
“…General health perception is a variable in the latent factor of health perception. In a Canadian study, older adults recently discharged from hospital with poor self-rated general health were 3.9 times more likely to have difficulty walking in the community compared to those with good self-rated general health [ 57 ]. A study in Japan found that there was a trend of a higher proportion of people with fair or poor self-rated health when the frequency of going outdoors was low [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…25 It has been suggested to describe a rehabilitation need based on an individual's self-reported health. 26 A disagreement in rehabilitation potential, however, can be noted between people's self-perception, which is influenced by their own awareness about rehabilitation services and their benefits, and health worker or carer assessment. 27 28 Even among health service sites, significant variations exist when conducting rehabilitation eligibility selection processes.…”
Section: What This Study Addsmentioning
confidence: 99%